Dynamic microRNA activity identifies therapeutic targets in trastuzumab‐resistant HER2+ breast cancer. Issue 10 (2nd August 2018) - Decker, Joseph T.; Hall, Matthew S.; Blaisdell, Rachel B.; Schwark, Kallen; Jeruss, Jacqueline S.; Shea, Lonnie D.
Abstract: MicroRNAs (miRNAs) are implicated in numerous physiologic and pathologic processes, such as the development of resistance to chemotherapy. Determining the role of miRNAs in these processes is often accomplished through measuring miRNA abundance by polymerase chain reaction, sequencing, or microarrays. We have developed a system for the large‐scale monitoring of dynamic miRNA activity and have applied this system to identify the contribution miRNA activity to the development of trastuzumab resistance in a cell model of HER2 + breast cancer. MiRNA activity measurements identified significantly different activity levels between BT474 cells (HER2 + breast cancer) and BT474R cells (HER2 + breast cancer cells selected for resistance to trastuzumab). We created a library of 32 miRNA reporter constructs, which were delivered by lentiviral transduction into cells, and miRNA activity was quantified by bioluminescence imaging. Upon treatment with the bioimmune therapy, trastuzumab, the activity of 11 miRNAs were significantly altered in parental BT474 cells, and 20 miRNAs had significantly altered activity in the therapy‐resistant BT474R cell line. A combination of statistical, network and classification analysis was applied to the dynamic data, which identified miR‐21 as a controlling factor in trastuzumab response. Our data suggested downregulation of miR‐21 activity was associated with resistance, which was confirmed in an additional HER2 + breast cancer cell line, SKBR3. Collectively, the dynamic miRNA activity measurements and analysis provided a system to identify new potential therapeutic targets in treatment‐resistant cancers. Abstract : MicroRNAs (miRNAs) are often dysrgulated in cancer and can give rise to drug resistance. Identifying the mechanisms for resistance may lead to new This work used an array of miRNA activity reporters to identify miR‐21 as a mediator of trastuzumab resistance in breast cancer.